Quality Evaluation and Comparison of Immunoglobulin Prepared by Two Various Methods of Human Plasma Fractionation: Quality Comparison of Two Fractionation Methods for Human Plasma-Derived IgG - Bagheri, Mehdi; Mohammadi Bidhendi, Sima; Khorsand Mohammad Pour, Hashem; Banazadeh, Soudabeh; Pourfatolah, Ali Akbar; Kokhaei, Parviz; Jalali, Seyed Mehrdad; Aghaie, Afsaneh (Iranian Journal of Pharmaceutical Sciences, 2020)
Based on European Pharmacopeia, there are some features which should be measured for any intravenous immunoglobulins prior to final release of the product. The most critical ones are the level of prekallikrein and anti-complementary activity in final formulation. For all commercial products, the national reference laboratory is prone to conduct such tests and there is no local report on quality control tests done on the products derived from Iranian human plasma. The study is to measure and control the international requirements such as prekallikrein count and anti-complementary activity for human intravenous immunoglobulins manufactured by local developed process in Iran in pilot scale. IgG-rich fraction was obtained by two fractionation methods. Cryoprecipitate was separated from tested fresh frozen plasma in both methods. In method I, for the next steps, fraction I paste, fraction II+III paste, and at the end, the fraction II paste were precipitated. In method II, the fraction I+II+III paste was simultaneously precipitated followed by deriving the fraction II paste. The paste obtained by both methods was separately subjected to the purification processes using anion and cation exchange chromatography followed by gel filtration and activity level of Prekallikrein in addition to anticomplement activity were compared with other laboratory evaluations. No difference was illustrated between protein and albumin content, pH, and conductivity of the two products. The fraction II paste obtained from both methods was measured and compared with each other. The IgG yield compared to the primary plasma was calculated as 4.6 and 4.3 g for the aforementioned methods respectively. The absence of impurities was determined by a strong IgG bond in electrophoresis while by HPLC, the dimer/ monomer content was measured more than 99% and the polymer/ aggregate was less than 1%. The amount of prekallikrein and total anticoagulant activity met the European Pharmacopoeia requirements for both methods